2019
DOI: 10.5539/jas.v11n3p565
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Phosphite and Water Deficit: Physiological Response of Eucalyptus Using Multivariate Analysis

Abstract: This study aimed to evaluate the physiological response of Eucalyptus citriodora Hook seedlings subjected to foliar application of potassium phosphite and water deficit with the aid of multivariate statistical analysis, using MANOVA and canonical discriminant analysis. The experiment was conducted in a completely randomized design with five treatments (0.0 L c.p. ha-1 of potassium phosphite with irrigation; 0.0; 1.25; 2.50 and 5.00 L c.p. ha-1 of potassium phosphite without irrigation) and six replicates, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…RNA-Seq showed that Phi's immune responses to heat stress were regulated by reprogramming global gene expressions (Xi et al, 2020). Recently, it was noticed that the Phi application enhanced the PS pigments and proline accumulation in leaves under waterdeficit stress with a value equal to those observed in irrigated control plants (Gonçalves et al, 2019). After the plant's exposure to abiotic stress, Phi increases the large number of proteins involved in cell wall formation as tolerance inducers.…”
Section: Phi-mediated Enhancement Of Plant Resistance To Abiotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-Seq showed that Phi's immune responses to heat stress were regulated by reprogramming global gene expressions (Xi et al, 2020). Recently, it was noticed that the Phi application enhanced the PS pigments and proline accumulation in leaves under waterdeficit stress with a value equal to those observed in irrigated control plants (Gonçalves et al, 2019). After the plant's exposure to abiotic stress, Phi increases the large number of proteins involved in cell wall formation as tolerance inducers.…”
Section: Phi-mediated Enhancement Of Plant Resistance To Abiotic Stressesmentioning
confidence: 99%
“…The interaction between plants and pathogens leads to physiochemical alteration in host plants. For example, photosynthesis reaction, respiration rate, and carbon uptake can be highly affected during pathogen infection ( Raggi, 1978 ; Gonçalves et al, 2019 ). Damages to chlorophyll, photosystem II (PS II), and other components of the electron transport chain lead to a remarkable decrease in transport of photosynthetic electron chains.…”
Section: Introductionmentioning
confidence: 99%